2019
DOI: 10.1021/acsaelm.9b00715
|View full text |Cite
|
Sign up to set email alerts
|

Optical Design of Inverted Pyramid Textured PERC Solar Cells

Abstract: Single side optical design of solar cells has limitations. In this paper, we studied the optical properties of inverted pyramid textured passivated emitter and rear cell (PERC) solar cells, considering different combinations of front and rear inverted pyramid angles. Ray tracing simulations were conducted to obtain a macro insight, and then experiments were performed under the conditions of practical applications. According to an analysis of the results, the overall optical properties are shown to be positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In addition, it is well known that the rear morphology also has a significant effect on rear surface passivation. Thus, for bi-PERC solar cells, the polishing degree of the rear pyramids is required to achieve a trade-off between front-side light trapping, rear-side light trapping, and rear surface passivation . Next, we focus on the further experimental study and analysis of the impact of various rear morphologies on the electrical performance of bi-PERC solar cells.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, it is well known that the rear morphology also has a significant effect on rear surface passivation. Thus, for bi-PERC solar cells, the polishing degree of the rear pyramids is required to achieve a trade-off between front-side light trapping, rear-side light trapping, and rear surface passivation . Next, we focus on the further experimental study and analysis of the impact of various rear morphologies on the electrical performance of bi-PERC solar cells.…”
Section: Results and Discussionmentioning
confidence: 99%
“…When the photovoltaic cell is connected to the forward bias voltage, the carrier balance is broken, so that the electrons and holes can pass through the PN junction and become unbalanced carriers. The unbalanced carriers compound with majority carriers and radiate outward; this is called electroluminescence [14], and is shown in Figure 1.…”
Section: Electroluminescencementioning
confidence: 99%
“…Our previous work indicated that the b-IP texture with a small θ in a range of 10.0 • -20.0 • can improve the optical gain of PERC compared with the quintessential 54.7 • . [39] The mass producible inverted pyramid structure fabricated by Cu-assisted chemical etching is usually bifacial texture. [40] On the other hand, θ can be gradually reduced by controllable single-side etching in HF/HNO 3 /H 2 O mixture, [39] which guarantees that the following simulation of the inverted pyramid textured TSCs with θ varying from 0.0 • to 54.7 • is instructive and practicable.…”
Section: Bottom Angle Of Rear-side Inverted Pyramidmentioning
confidence: 99%
“…Our previous work have illustrated that when θ > 4 • , the reflection in the front interface of TSCs will generally decrease with the increase of θ because of the enhanced probability of total internal reflection; when θ < 24 • , the transmission in the rear interface of TSC will be suppressed for the same reason. [39] Therefore, a small θ can make a trade-off between reflection and transmission, contributing to a higher J G Si . Thus, in order to maximize the optical harvest in PVK/Si TSCs, the rear side texture should become smoother, which will be simultaneously beneficial to the passivation of the rearside surface of Si subcell.…”
Section: Bottom Angle Of Rear-side Inverted Pyramidmentioning
confidence: 99%